2014
DOI: 10.3390/molecules191118179
|View full text |Cite
|
Sign up to set email alerts
|

Icariin Is A PPARα Activator Inducing Lipid Metabolic Gene Expression in Mice

Abstract: Abstract:Icariin is effective in the treatment of hyperlipidemia. To understand the effect of icariin on lipid metabolism, effects of icariin on PPARα and its target genes were investigated. Mice were treated orally with icariin at doses of 0, 100, 200, and 400 mg/kg, or clofibrate (500 mg/kg) for five days. Liver total RNA was isolated and the expressions of PPARα and lipid metabolism genes were examined. PPARα and its marker genes Cyp4a10 and Cyp4a14 were induced 2-4 fold by icariin, and 4-8 fold by clofibra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…Our results showed that hispidulin significantly enhanced the gene expression of these four enzymes, suggesting stimulation of mitochondrial FA β-oxidation. Previous studies have showed that elevated expression of CPT1α, HMGCS2, Acat1 and Acad1 was responsible for the hypolipidemic effect of natural compound such as icariin and oxymatrine [24,34]. Consistently, our results here also indicate that enhancement of mitochondrial FA β-oxidation contributes to hispidulin induced hypolipidemic effects.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results showed that hispidulin significantly enhanced the gene expression of these four enzymes, suggesting stimulation of mitochondrial FA β-oxidation. Previous studies have showed that elevated expression of CPT1α, HMGCS2, Acat1 and Acad1 was responsible for the hypolipidemic effect of natural compound such as icariin and oxymatrine [24,34]. Consistently, our results here also indicate that enhancement of mitochondrial FA β-oxidation contributes to hispidulin induced hypolipidemic effects.…”
Section: Discussionsupporting
confidence: 91%
“…Total RNA in rat liver tissue was extracted using a commercial kit (RNeasy Mini kit, Qiagen, Dusseldorf, Germany) and the primers for enzymes were synthesized by Sangon Biotech (Shanghai, China) based on published sequence [24]. First-strand cDNA was synthesized from 1 μg RNA using the Reverse Transcription System (Takara, Dalian, China) according to the manufacturer's instructions and PCR was performed using SYBR GREEN mastermix (Solarbio Co., Beijing, China).…”
Section: Quantitative Real-time Rt-pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, icariin has been reported to ameliorate streptozocin-induced rat diabetic retinopathy and nephropathy (31,32). A previous study demonstrated that icariin could serve as a peroxisome proliferator-activated receptor α agonist, which activates gene expression associated with lipid metabolism in the liver to contribute towards diabetes management (33). In the present study, it was revealed that icariin is able to prevent cytokine-induced β-cell death, which is an important cause of T1DM.…”
Section: Discussionsupporting
confidence: 50%
“…Icariin also ameliorated streptozocin-induced rat diabetic retinopathy 52 and nephropathy 53 . The recent study conducted by Lu et al also indicated that icariin was a novel PPAR agonist, activated lipid metabolism gene expression in liver, which could be a basis for its lipid-lowing effects and its beneficial effects against diabetes 54 . It was reported that old mice were significantly heavier than young mice, mostly because of an increase in fat mass and had a tendency to decreased energy expenditure 47 .…”
Section: Accepted Manuscriptmentioning
confidence: 97%